Acute effects of concentric and eccentric exercise on glucose metabolism and interleukin-6 concentration in healthy males - Philippe, M; Krüsmann, PJ; Mersa, L; Eder, EM; Gatterer, H; Melmer, A; Ebenbichler, C; Burtscher, M (Biology of Sport, 2016)
Acute muscle-damaging eccentric exercise (EE) negatively affects glucose metabolism. On the other hand, long-term eccentric endurance exercise seems to result in equal or superior positive effects on glucose metabolism compared to concentric endurance exercise. However, it is not known if acute non-muscle-damaging EE will have the same positive effects on glucose metabolism as acute concentric exercise (CE). Interleukin-6 (IL-6) released from the exercising muscles may be involved in the acute adaptations of glucose metabolism after CE and non-muscle-damaging EE. The aim of this study was to assess acute effects of uphill walking (CE) and non-muscle-damaging downhill walking (EE) on glucose metabolism and IL-6 secretion. Seven sedentary non-smoking, healthy males participated in a crossover trial consisting of a 1 h uphill (CE) and a 1 h downhill (EE) walking block on a treadmill. Venous blood samples were drawn before (pre), directly after (acute) and 24 h after (post) exercise. An oral glucose tolerance test (OGTT) was performed before and 24 h after exercise. Glucose tolerance after 1 and 2 hours significantly improved 24 hours after CE (-10.12±3.22%: P=0.039; -13.40±8.24%: P=0.028). After EE only the 1-hour value was improved (-5.03±5.48%: P=0.043). Acute IL-6 concentration rose significantly after CE but not after EE. We conclude that both a single bout of CE and a single bout of non-muscle-damaging EE elicit positive changes in glucose tolerance even in young, healthy subjects. Our experiment indicates that the overall metabolic cost is a major trigger for acute adaptations of glucose tolerance after exercise, but only the IL-6 production during EE was closely related to changes in glycaemic control.